A study of uterine balloon tamponade for the management postpartum haemorrhage using Bakri balloon - Patil, Shashikala B.; K., Indumathi H.; ., Sarojini; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: PPH is the most common cause of maternal morbidity and mortality around the world. Incidence of PPH is 2-4% following vaginal delivery and 6% following cesarean delivery in India. Uterine atony is the most common cause of PPH. Treatment of PPH involves medical treatment and surgical management. In between medical and surgical management of PPH comes uterine balloon tamponade which is simple, less invasive and can be managed with minimal training. Methods: A retrospective cohort study was done for 2 years at Vanivilas hospital, Bangalore medical college and research centre, Bangalore, Karnataka. Cases of atonic PPH managed using Bakri balloon were included in the study. The objective of the study was to study the effectiveness of uterine balloon tamponade using Bakri balloon in the management of atonic PPH and to study the maternal outcome. Results: In this study total of 50 cases were included. Women were in the age group of 18 to 33years. Regarding obstetric history, 22 (44%) were primigravida and 28 (56%) was multigravida. Among these 50 cases 8 (16%) women had undergone caesarean delivery and 42(84%) had vaginal delivery. All women received blood transfusion, 17 (34%) received blood and blood components (like PRBC, FFP AND platelets) and 33 (66%) cases received only PRBC transfusion. In these 50 cases, 32 (64%) required ICU admission for monitoring, remaining 18 (36%) were monitored in the labor-room. Bakri balloon was effective in 49 cases among 50. Success rate was 98%. Conclusions: Intrauterine balloon tamponade using Bakri balloon is effective for control of atonic PPH in majority of cases.